Prognostic implications of right ventricular to pulmonary artery uncoupling in cardiac amyloidosis - Jakstaite, Aiste Monika; Hänselmann, Anja; Soltani, Samira; Angelini, Eleonora; Heuser, Michael; Gödecke, Vega; Gingele, Stefan; Skripuletz, Thomas; Bauersachs, Johann; Bavendiek, Udo; Berliner, Dominik (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRight ventricular–pulmonary arterial (RV–PA) uncoupling in cardiac amyloidosis (CA) has been underexplored, with focus mainly on tricuspid annular plane systolic excursion (TAPSE)/pulmonary artery systolic pressure (PASP). This study aims to evaluate the association of various echocardiographic surrogates of RV–PA coupling with outcomes in cardiac transthyretin (ATTR-CA) and light-chain (AL-CA) amyloidosis.MethodsWe analyzed RV–PA coupling in patients diagnosed with ATTR-CA and AL-CA at our center between 2014 and 2023. RV–PA coupling was assessed using TAPSE/PASP, fractional area change (FAC)/PASP, and RV free wall strain (RVFWS)/PASP. The primary endpoint was all-cause mortality.ResultsA total of 120 patients (86% ATTR-CA, 14% AL-CA) were included in the study (median age 77 years, 88% male). During a median follow-up period of 23 (IQR: 15–34) months, the primary endpoint occurred in 25 patients (21%). The study population was stratified based on the ROC-derived TAPSE/PASP cutoff of <0.30 mm/mmHg, demonstrating RV–PA uncoupling. Lower RV–PA coupling surrogates were independently associated with higher mortality (HR per +0.1 unit: TAPSE/PASP, 0.74, 95% CI: 0.59–0.93, p = 0.011; FAC/PASP, 0.87, 0.77–0.98, p = 0.018; RVFWS/PASP, 0.78, 0.63–0.97, p = 0.024). TAPSE/PASP demonstrated the strongest prognostic discrimination (AUC: 0.79, bootstrapped 95% CI: 0.66–0.91), compared with FAC/PASP (AUC: 0.75, 0.58–0.91) and RVFWS/PASP (AUC: 0.72, 0.52–0.87).ConclusionsRV–PA uncoupling may be linked to a higher risk of all-cause mortality in CA. TAPSE/PASP outperformed numerically FAC/PASP and RVFWS/PASP in predicting long-term survival, although it did not clearly outperform established RV function parameters.